FAKTOR-FAKTOR YANG MEMENGARUHI PERUSAHAAN MELAKUKAN PERGANTIAN AUDITOR DAN KONSEKUENSINYA TERHADAP AUDIT DELAY - Firanty, Ria; Syam, M Ardiansyah (Jurnal Akuntansi, 2015)
This study uses two research models. Data processing and testing hypotheses using logistic regression models for the first model and multiple linear regression for the second models are then processed using the program Statistical Package for Social Science (SPSS) version 16.0 with a significance value was set at 5%. The sample used in this study was 204 data of manufacturing companies listed in the Indonesian Stock Exchange in the period  2008 to 2011. Sample selection was done by using simple random sampling. The results of the first model analysis shows that the level of profitability positively influence auditor switching and size of Public Accounting Firm negatively influence auditor switching. The results of the second model analysis shows that the company's financial condition has a negative impact on audit delay and auditor switching has no influence on audit delay.